2004
DOI: 10.1097/01.ju.0000099891.68488.4e
|View full text |Cite
|
Sign up to set email alerts
|

Questionable Efficacy of Extracorporeal Shock Wave Therapy for Peyronie’s Disease:: Results of a Prospective Approach

Abstract: According to our data ESWT does not appear to be significantly effective for decreasing penile curvature and plaque size or improving sexual function in the total population of patients with Peyronie's disease despite improvements in individuals. Penile pain seems to resolve earlier than during the natural course. Regarding the results of this study and previous reports with exact documentation of the clinical findings it can be concluded that ESWT cannot be recommended as a standard procedure for Peyronie's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 18 publications
2
37
0
3
Order By: Relevance
“…The few studies that have reported on the effects of ESWT on penile rigidity have failed to find a difference. 14,19,20 Given the availability and efficacy 21 of medical therapies for ED, it is our practice to offer these methods to men with combined PD and erectile dysfunction prior to considering ESWT. Those who show a good response and achieve near-normal penile rigidity are offered ESWT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that have reported on the effects of ESWT on penile rigidity have failed to find a difference. 14,19,20 Given the availability and efficacy 21 of medical therapies for ED, it is our practice to offer these methods to men with combined PD and erectile dysfunction prior to considering ESWT. Those who show a good response and achieve near-normal penile rigidity are offered ESWT.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Although there appears to be an overall benefit from EWST, some studies have noticed significant variations in response. For example, Hauck and associates 14 found no improvement in their group as a whole but noticed a "remarkable decrease in curvature" in 30% of their patients. Manikandan and colleagues 15 found that although 14% of their patients reported excellent results and 50% significant improvements, the remainder saw little or no benefit.…”
Section: Introduction P Eyronie's Disease (Pd) Is a Benign Afflictionmentioning
confidence: 94%
“…[2][3][4][5][6][7][8][9][10][11] Many of the studies have been criticized for their lack of objectivity and relatively short follow-up periods (mean follow-up 1-9 months), and there is, therefore, a paucity of longterm data with regard to therapy effectiveness and safety. There also is a lack of information regarding the long-term durability of the response after initial success.…”
Section: Srirangam Et Al 882mentioning
confidence: 99%
“…The use of extracorporeal shockwave therapy (ESWT) for Peyronie's disease was introduced by Bellorofonte and associates 1 as a conservative option, and since then, numerous reports have addressed the efficacy of this treatment. [2][3][4][5][6][7][8][9][10][11] Reported results have been discordant, with some showing promising responses to ESWT with reductions in deformity, plaque size, and pain and concurrent improvement in sexual function, whereas others demonstrate no significant benefit. 8,10,11 In spite of reports of success and low complication rates, previous studies have been criticized for small patient numbers, absence of a control arm, use of subjective outcome measures, and lack of long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Bezüglich der Symptome Plaquegröße,Rückbildung der Schmerzen und Verbesserung der Sexualfunktion bestand kein signifikanter Unterschied zur Kontrollgruppe [1]. Die Langzeitauswertung der Ergebnisse (prospektive, unkontrollierte Studie) eines großen Kollektives kommt zu dem Ergebnis,dass es für die Gesamtpopulation keine signifikante Besserung der Deviation, der Plaquegröße und der sexuellen Funktion trotz signifikanter Besserungen in Einzelfällen gibt [2]. Die Patienten werden aber nach ESWT schneller schmerzfrei als nach dem natürlichen Krankheitsverlauf zu erwarten.…”
Section: Klinische Studienunclassified